2021
DOI: 10.4064/fm710-11-2020
|View full text |Cite
|
Sign up to set email alerts
|

On genericity of shadowing in one dimension

Abstract: We show that shadowing is a generic property among continuous maps and surjections on a large class of locally connected one-dimensional dynamical systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…As mentioned in the introduction, there is a significant body of work devoted to determining the prevalence of shadowing in C(X) for various categories of topological spaces X. In particular, shadowing has been shown to be a generic property of dynamical systems on manifolds ( [23,17,20,15,11]), dendrites ( [2]), and more exotic locally connected continua ( [12]). In addition, shadowing has been shown to be generic in the space of surjections (S(X)) on spaces in those classes.…”
Section: Rigid Spaces and Shadowingmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned in the introduction, there is a significant body of work devoted to determining the prevalence of shadowing in C(X) for various categories of topological spaces X. In particular, shadowing has been shown to be a generic property of dynamical systems on manifolds ( [23,17,20,15,11]), dendrites ( [2]), and more exotic locally connected continua ( [12]). In addition, shadowing has been shown to be generic in the space of surjections (S(X)) on spaces in those classes.…”
Section: Rigid Spaces and Shadowingmentioning
confidence: 99%
“…In particular, in [12] we asked whether there were, in fact any continua X such that shadowing is not generic in C(X).…”
Section: These Examples Allow Us To Answer a Few Open Questions Conce...mentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, it has been observed that shadowing plays an important role in stability theory [21,23,25] and in characterizing ω-limit sets [1,2,14]. Shadowing has also been shown to be a relatively common property in the space of dynamical systems on certain classes of spaces [5,11,13,15,16,22,26].…”
Section: Introductionmentioning
confidence: 99%
“…The shadowing property has wide-reaching applications in the analysis of dynamical systems, especially in analyzing stability [21,23,24] and in characterizing ω-limit sets [3,16]. Despite being a relatively strong property, shadowing is a generic property in the space of dynamical systems on many spaces [4,12,14,22].…”
mentioning
confidence: 99%